Produção e caracterização de dosímetros à base de magnésio - Souza, Luiza Freire de (2012)
With the purpose of obtain solid state dosimeters whith characteristics such as high sensitivity, ease obtaining and handling and that are practical and economical were studied in in the present work phosphors based on magnesium ion. The materials chosen for analysis were MgSO4 (magnesium sulphate) and MgB4O7 (magnesium tetraborate), both materials were doped with the rare earths Dy (dysprosium) and Tm (thulium). The interest in the production of these doped materials was to investigate the production of thermoluminescent dosimeters with these elements and study their thermoluminescence characteristics. The phosphors were obtained by acid solution. The thermoluminescence response of materials produced in pellet form were investigated. For the study of thermoluminescent characteristics, sulphate and tetraborate samples were irradiated with a beta source (90Sr+90Y). The thermoluminescence response of the pellets based on MgB4O7 were investigate in more details after exposure to different radiation sources such as X rays , 60Co and 137Cs. For these materials the dose response curves related to X-rays and 60Co irradiations, reproducibility, homogeneity, minimum detectable dose, energy dependence, the intrinsic efficiency and the kinetic parameters for the glow curves, using Chen´s method were evaluated. The results obtained for MgB4O7:Dy and MgB4O7:Tm samples, show that is possible to use both materials to radiation dosimetry of photon beams such as X ray and gamma and beta radiation, due to the facility of the preparation , since they have adequate sensitivity and linearity of TL response over the dose range evaluated, among other characteristic. The initial studies of MgSO4: Dy (or Tm), show that materials have potential to dosimetry and should be better evaluated in future work.